Fragmentation of C2H22+ in collisions with 100 eV electrons. (20th July 2018) - Luo, D; Wei, B; Zhang, Y; Zou, Y; Hutton, R; Chen, F; Wang, X
Abstract: The fragmentation of C2 H2 2+ dications following 100 eV electron impact double ionization of acetylene was studied experimentally using a cold target recoil-ion momentum spectroscopy. A weak extraction field was adopted to increase the experimental resolution. Meanwhile, as a consequence of the large momentum generated by the Coulomb repulsive force, the particles which have similar charge to mass ratio such as C + and CH + cannot be distinguished directly from the time of flight. In order to obtain a comprehensive understanding of the experimental results, a Monte Carlo (M-C) method was used to simulate the time of flight under experimental conditions. With the help of the M-C method, four reaction channels, the Coulomb explosion of the doubly charged parent ions C2 H2 2+ into the fragment ions CH + + CH +, C + + CH + 2, C + + CH +, C + + C +, were simulated and the kinetic energy release (KER) distributions were deduced. In particular, the structure of fragmentation channel to C + + CH + represents a typical feature of the absence of hydrogen migration, which was not observed in previous studies. The KER in the fragmentation reaction of C2 H2 2+ has been used to obtain precursor state energy for the formation of product ion pairs. In general, good agreement was achieved between our KER results and available experimental data in previous works.